Variabilitas suhu laut pada kejadian IOD (Indian Ocean Dipole) di perairan barat Sumatera menggunakan data Argo Float - Hanani Adiwira; Noir P. Purba; Syawaludin A. Harahap; Mega L. Syamsuddin (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2018)
The objective of the research was to analyze the vertical variability of the water column in the West Sumatra waters. The data used to analyze the vertical variability was the temperature data sets from Argo float instruments which were operated from 2009 to 2011 in the West Sumatran sea region. The secondary data that used was the geostrophic current data sets which obtained from the Jason image satellite also sea temperature anomaly data. The method used in this research is by analyzing temporally and spatially and then describing while comparing the data. The result of the research showed that IOD formed from June to July with the peak of IOD was from September to November and the disintegration starts in December. The SST average on 2009 (Neutral IOD) during peak phase of IOD was 29.060C, in 2010 (Negative IOD) the SST mean is 28.690C, in 2011 (Positive IOD) the SST mean was 28.790C. The result from spatial analyzes showed that the strong IOD was the main reason for the movement of the mixed layer in West Sumatra waters, so the warm water cannot be found around the West Sumatra waters. The upper boundary depth of thermocline during peak phase of 2009s neutral IOD starts from September was on 82.59 m, in October was 86.12 m and in November was 89.5 m. In Septemeber 2010 the upper thermocline boundary was found on 89.06 m deep, in October was 104.05 m, and in November was 107.36 m, the thermocline got deeper because the input of water masses from West Indian Ocean intensifies because of negative IOD event. In September 2011 the upper thermocline boundary was found on 64.16 m, in October was 75.35 m and in November was 79.88 m. The thermocline found more shallow because the mixed layer on East Indian Ocean moved westward so the thermocline lifted up to fill the water column emptiness.Penelitian ini bertujuan mengkaji variabilitas kolom air secara vertikal di perairan Barat Sumatera. Data yang digunakan yaitu data suhu dari instrumen Argo float yang beroperasi di perairan Barat Sumatera tahun 2009 2011. Data pendukung yaitu data arus geostropik yang diperoleh yang diperoleh dari citra Jason selain itu digunakan data suhu anomali laut. Metode yang digunakan adalah analisis temporal dan spasial serta deskriptif komparatif. Hasil penelitian menunjukkan proses pembentukan IOD terjadi pada Juni Agustus kemudian mencapai puncak pada September November dan proses peluruhannya pada Desember. Rata rata SPL pada fase puncak tahun 2009 (IOD netral) yaitu 29.060C; pada 2010 (IOD negatif) yaitu 28.690C; dan pada 2011 (IOD positif) yaitu 28.790C. Berdasarkan analisis spasial IOD dengan intensitas kuat mengakibatkan pergerakan massa air hangat melewati perairan Barat Sumatera sehingga tidak terdeteksi lagi di lokasi ini. Batas atas termoklin pada fase puncak IOD 2009 (September) yaitu 82.59 m; Oktober sekitar 86.12 m dan November mencapai 89.5 m. Selanjutnya pada 2010 yaitu pada September sekitar 89.06 m; Oktober sekitar 104.05 m dan November mencapai 107.36 m. Terlihat, termoklin semakin dalam karena massa air hangat dari Hindia Barat yang mengisi perairan Barat Sumatera menjadi semakin kuat pada fase IOD negatif. Sebaliknya, pada September 2011 termoklin berada pada kedalaman 64.16 m; Oktober pada kedalaman 75.35 m dan November sekitar 79.88 m. Pada periode ini termoklin terdeteksi lebih dangkal karena lapisan mixed layer bergerak ke Hindia Barat dan kekosongannya diisi lapisan termoklin.